Design of a wideband square slot bandpass frequency‐selective surface using phase range analysis. Issue 1 (5th January 2020) - Singh, Chitra; Jha, Kumud R.; Sharma, Satish K.; Jibran, Zahoor A. Pandit; Singh, Ghanshyam
Abstract : This article presents the design of a wideband bandpass frequency‐selective surface (FSS). The structure is designed using the analysis of the generalized scattering matrix (GSM)‐based transmission phase range. A relationship between the transmission phase range and the bandpass fractional bandwidth (FBW) is developed. The analysis reveals that the FBW of the FSS unit‐cell is proportional to the phase range. Based on the interpretation of results, a design curve has been drawn, and using this curve, a simple square slot FSS on a low‐cost FR‐4 substrate has been fabricated and measured. Using the design curve, a 53% FBW has been predicted. The simulated results show a 52% FBW with the 3.52‐GHz center frequency ( f o ). The response for the transverse electric (TE) and transverse magnetic (TM) modes has been measured. The structure has a bandpass FBW equal to 50% and 53.3% in TE and TM modes, respectively. The method presented in this article may be used to increase the bandpass response of different FSS topologies. Abstract : This paper presents the design of a wideband bandpass frequency selective surface (FSS). The structure is designed using the analysis of the generalised scattering matrix based (GSM) transmission phase range.